2018
DOI: 10.5006/2807
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Observations of Early Stage Oxidation of Ni-Cr and Ni-Cr-Mo Alloys

Abstract: Results of in situ transmission electron microscopy experiments on the early stage oxidation of Ni-Cr and Ni-Cr-Mo alloys are reported. An epitaxial rock-salt oxide with compositions outside the conventional solubility limits initiated at the surface of both alloys, progressing by a layer-by-layer mode. Kirkendall voids were found in Ni-Cr alloys near the metal/oxide interface, but were not seen in the Ni-Cr-Mo. The voids initiated in the oxide then diffused to the metal/oxide interface, driven by the misfit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 53 publications
2
28
1
Order By: Relevance
“…This was in agreement with studies on the early stages of oxidation on binary alloys where it was shown that the first oxides formed were nickel, nucleated as islands distributed across the surface of the specimen [4][5][6][7]. It has also been shown that a metastable chromium-oxygen phase formed on the surface of binary alloys, surrounding the NiO islands [5][6][7][8][9]. Examination of the surface of the specimens after the heating stage, Fig.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This was in agreement with studies on the early stages of oxidation on binary alloys where it was shown that the first oxides formed were nickel, nucleated as islands distributed across the surface of the specimen [4][5][6][7]. It has also been shown that a metastable chromium-oxygen phase formed on the surface of binary alloys, surrounding the NiO islands [5][6][7][8][9]. Examination of the surface of the specimens after the heating stage, Fig.…”
Section: Discussionsupporting
confidence: 90%
“…The influence of other alloying elements on the stability of the oxide also needs also to be considered, e.g. molybdenum has been shown to stabilise this oxide on simple nickel alloys [9] and is present in the current alloy, Table 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations